Hand Gesture Recognition Using Artificial Neural Networks - Mustafa, Mohd Amrallah (2007)
Hand gesture has been part of human communication, where, young children usually communicate by using gesture before they can talk. Adults may have to also gesture if they need to or they are indeed mute or deaf. Thus the idea of teaching a machine to also learn gestures is very appealing due to its unique mode of communications. A reliable hand gesture recognition system will make the remote control become obsolete. However, many of the new techniques proposed are complicated to be implemented in real time, especially as a human machine interface.